Optimizing epilepsy treatment in children, adults and elderly: clinical perspectives - Satishchandra, Parthasarthy; Shah, Sudhir V.; Renjen, Pushpendra N. (International Journal of Research in Medical Sciences, 2022)
Epilepsy is a common neurological condition among all age groups. Its diagnosis depends on clinical history and is supported by investigations like electroencephalograph and magnetic resonance imaging. In children, febrile seizures and juvenile myoclonic seizures are common. In adults and elderly, epilepsy could be new onset or present since childhood. Several antiseizure medications (ASMs) are available for treatment of epilepsy. Each of these drugs has different advantages as well as limitations. Several factors including patient related factors (e. g. age, comorbidities, and gender), seizure characteristics and epilepsy type, and drug related factors (namely, pharmacokinetics, pharmacodynamics, efficacy, side effects, and risk of drug-drug interactions) are considered while selecting drug therapy. There are concerns related to teratogenicity due to pharmacotherapy in females of child-bearing potential. Elderly patients also need special considerations while selecting an appropriate treatment option for epilepsy. Advisory board meetings with a group of expert neurologists were conducted at eight cities across India to gain clinical insights on management of epilepsy in different age groups. Consensus was supported by relevant literature obtained from PubMed and Google scholar using the keywords ‘epilepsy’, ‘diagnosis’, ‘children’, ‘adults’, ‘elderly’, and ‘management’. According to the experts, choice of appropriate ASM is driven by patient- and drug-related factors and seizure characteristics. In India, valproate remains a commonly prescribed agent except in females of childbearing age. Levetiracetam is preferred because of its safety profile whereas clobazam is an effective initial add-on therapy. Newer drugs are largely useful as adjuvants.